Evaluation of in-house ELISA using Trypanosoma cruzi lysate and recombinant antigens for diagnosis of chagas disease and discrimination of its clinical forms - Longhi, Silvia Andrea (2012)
The aim of this work was to investigate the potential usefulness of Trypanosoma cruzi lysate, recombinant protein JL7, and peptides P013, R13, JL18, JL19, and P0b as serological markers for human Chagas disease. We analyzed 228 sera from Brazilian Chagas disease patients classified into four clinical groups and 108 from non-chagasic patients. We defined the diagnostic sensitivity, specificity, and Kappa index measured by enzyme-linked immunosorbent assay (ELISA). As previously described, the highest values of diagnostic parameters were achieved for T. cruzi lysate and JL7; peptide P013 showed high specificity but low sensitivity. The other peptides resulted in lower sensitivity and specificity in our ELISA than T. cruzi lysate and JL7 protein. Antibodies against JL7 protein were mainly detected in sera from patients with severe chagasic cardiomyopathy, compared with those from the indeterminate form, whereas peptides failed to discriminate between the clinical forms of the disease.